Analisis Penerapan Prinsip Akuntansi Terhadap Akuntabilitas Laporan Keuangan Masjid (Studi Kasus Masjid Desa Bandar Khalipah) - Muhammad Syukri Nasution; Junita Putri Rajana (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
Mosque is one form of non-profit organization or organization that does not expect profit (non profit oriented). Therefore, mosques as a means of worship and activities of the ummah require effective financial reporting, this is because to support worship and religious activities. The results showed that the application of accounting principles had a huge effect on accountability or accountability of mosque financial statements. The results of interviews from various sources can be known that accounting principles have been applied to the creation of the mosque's financial statements. So that the mosque administrator has managed finances openly as a form of accountability or financial accountability of the mosque by recording receipts and cash expenditures. Financial management is well recorded even though it is still simple. Related to PSAK 45, the mosque administrator has not recorded based on PSAK 45 because the standard is recognized to have never been heard and introduced to the mosque administrator.